Contextual Semantics of the Title of Michail Shishkin’s Novel “The Capture of Izmail” - Shafranskaya, Eleonora (Respectus Philologicus, 2016)
The article deals with the interconnections between the title and context of Michail Shishkin’s novel “The Capture of Izmail”. Such concepts as “chronotopos”, “truth”, “time”, “moment of time” and “historical trauma” are examined in interrelation, too. A precedent text, “The Capture of Izmail” is looked upon symbolically, like a huge historical deception. Instead of relying on well-known historical landmarks or widely reported cataclysms, Shishkin puts forward a new set of patterns; citing A. Etkind, this is “not a history of events, but a history of humans and texts in their mutual interaction”, – that is, an approach qualified in American literary theory as the new historicism. In the novel’s context, the fact of Izmail’s capture designates a new vector of history understanding, both private and common. When a photographer uses cliché “Say cheese!”, the person is supposed to smile, and this alleged smile appears as a symbol of falsehood which became a norm both in society and in history. According to Shishkin, time should be counted by its moments consisting of personal facts, names and places. Perhaps, that is the way to get rid of historical traumas and, applying Etkind’s metaphor about “the crooked grief”, to straighten it so that the grief would be merged into a “solid state”. Russia, Shishkin seems to believe, stands in need to apply this very approach to history understanding.